PELATIHAN DAN PENDAMPINGAN KETERAMPILAN MASASE OLAHRAGA DASAR BAGI MAHASISWA SEMESTER 1 UNTUK MENINGKATKAN PELAYANAN P3K PADA PRODI PENJASKESREK UNIVERSITAS PGRI MAHADEWA INDONESIA TAHUN AJARAN GANJIL 2021/2022 - Komang Ayu Tri Widhiyanti; Ni Wayan Ary Rusitayanti; Ni Wayan Ariawati; Ni Luh Putu Indrawathi (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
The background of this training is because new students' knowledge of sports massage is still not optimal and there are still many mistakes made in handling sports injuries so that it will result in the recovery of these injuries. Factors that can be identified as the cause of the problem include the fact that students tend to have never received integrated massage skills training which consists of: sports massage, sports injury massage, and healing massage. The purpose of the training is to equip students with sports massage skills, sports injuries, and healing to reduce the risk from the effects of sports activities so as to make it easier to do first aid. The methods used are: demonstrations, exercises, and assignments combined with mentoring. The target of the training is all semester 1 students of the Penjaskesrek study program, Universitas PGRI Mahadewa Indonesia, for the odd academic year 2021/2022, totaling 56 people. The conclusions of this training are: (1) Semester 1 students of the PENJASKESREK study program at the University of PGRI Mahadewa Indonesia for the Odd Academic Year 2021/2022 have gained integrated massage knowledge and skills; (2) The results/scores achieved from 56 participants are: 33 or 57.78% getting an A or very good, 23 or 42.22% getting a B or good; (b) The average percentage of mastery of the training material is 82.24% or in good category.